Diabetic dyslipidemia and type 2 diabetes mellitus as early as six weeks post-partum: a nested case control study - Iqbal, Meesha; Gill, Paramjit; Azam, Iqbal; Iqbal, Romaina (International Journal Of Community Medicine And Public Health, 2021)
Women who develop diabetes during pregnancy (Gestational diabetes mellitus-GDM) increase their risk of developing type 2 diabetes mellitus (T2DM) post-partum by 70%. The average time to develop T2DM varies and is not widely studied. T2DM is associated with increased risk of developing dyslipidemia leading to cardiovascular diseases. We intended to study the association of dyslipidemia and T2DM as early as 6 weeks post-partum. A matched case control study was designed, and conditional logistic regression analysis applied to get adjusted matched odds with 95% confidence intervals. Our study revealed increased serum LDL levels in the cases compared to the controls (p=0.03). However, no association was seen with other lipid parameters.